POPULATION AGEING: TRENDS AND IMPACT ON THE STRUCTURE OF THE NATIONAL ECONOMY - Hayda, Yuriy; Dluhopolska, Tetiana; Tsyapa, Nazar (Socio-economic relations in the digital society, 2025)
The ageing of the population is one of the key demographic challenges in Ukraine, significantly impacting the economy, social systems, and labour market. This article examines the dynamics of this process and its consequences for the state budget, pension provision, and social policy. The primary objective of the study is to analyse the dynamics of population ageing in Ukraine and assess its impact on key economic indicators to determine strategies for mitigating its negative effects on the country's economy. The main method chosen for the study is correlation analysis, although comparative analysis, systematization, and formalization methods were also utilized. The research analyses major theories of population ageing, including the disengagement theory, activity theory, subcultural theory, age stratification theory, and symbolic interactionism theory. Special attention is given to the impact of war on demographic changes, particularly the decline in birth rates, increased mortality, and mass emigration. Forecast models of the impact of population ageing on the economy of Ukraine in war conditions have been developed under optimistic and pessimistic scenarios. The study's findings highlight the need for pension system reform, stimulation of labour activity among older individuals, and the implementation of comprehensive socio-economic strategies to minimize the negative consequences of population ageing.
Keywords: population aging; life expectancy; retiree; social protection; correlation analysis; forecasting